Adrenal insufficiency and bilateral adrenal enlargement: demonstration by computed tomography. Issue 715 (May 1985) - Wheatley, T.; Gallagher, S.; Dixon, A. K.
Abstract : A patient presented with fever, malaise and a staphylococcal wound infection occurring 3 weeks after severe haemorrhage from a lacerated brachial artery. There were no clinical features to suggest Addison's disease but abdominal computed tomography to exclude abdominal sepsis showed bilateral adrenal gland enlargement with preservation of adrenal shape. This was consistent with resolving adrenal haemorrhage or infarction and endocrinological investigations confirmed primary adrenal failure.